Analyzing the Relationship between Language and Identity (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research explores the link between one's language and their sense of self. We have the incredible capacity to convey not only our ideas and identities but also the distinctiveness of each person's language, since there are more than seven thousand languages spoken today. This is a big part of who we are as humans. by which we may express our own personality in every given society. Words, spoken language, and written language are the three fundamental building blocks of language.The written and spoken word transmits all of the aforementioned—our ideas, culture, society, objectives, and even our authentic and idealized selves. The personalities we embody and construct might change depending on the occasion. I prepared a poll and sent it out over many channels to make sure I could get data from a wide range of individuals with different backgrounds. For the sake of precision, it included multiple-choice answers, and for the purpose of self-evaluation, it included closed-ended questions with space for free-form writing. People of all ages were randomly chosen to take part in the survey, and graphs were made to show some of the statistical data that came from the questions. As we said before, the setting was a number of social networking programmes. Hopefully, this research will help to clarify the complex relationship between language and identity.